2005
DOI: 10.1074/jbc.m410605200
|View full text |Cite
|
Sign up to set email alerts
|

A Streptococcal Collagen-like Protein Interacts with the α2β1 Integrin and Induces Intracellular Signaling

Abstract: The streptococcal collagen-like proteins Scl1 and Scl2 are prokaryotic members of a large protein family with domains containing the repeating amino acid sequence (Gly-Xaa-Yaa) n that form a collagen-like triple-helical structure. Here, we test the hypothesis that Scl variant might interact with mammalian collagen-binding integrins. We show that the recombinant Scl protein p176 promotes adhesion and spreading of human lung fibroblast cells through an ␣ 2 ␤ 1 integrin-mediated interaction as shown in cell adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 56 publications
1
107
0
Order By: Relevance
“…Mapping of ␣ 2 ␤ 1 Integrin Binding Region in rScl1-Our previous study reported binding between the CL region of the recombinant P176 construct, derived from Scl1.41 protein, and the ␣ 2 ␤ 1 integrin on human fibroblasts (20); however, the integrin-binding motif on P176 was not defined. To map the ␣ 2 ␤ 1 integrin binding site of P176 we inserted fragments of the P176-CL region into the integrin binding-negative protein, P163 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mapping of ␣ 2 ␤ 1 Integrin Binding Region in rScl1-Our previous study reported binding between the CL region of the recombinant P176 construct, derived from Scl1.41 protein, and the ␣ 2 ␤ 1 integrin on human fibroblasts (20); however, the integrin-binding motif on P176 was not defined. To map the ␣ 2 ␤ 1 integrin binding site of P176 we inserted fragments of the P176-CL region into the integrin binding-negative protein, P163 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Rotary Shadowing and Electron Microscopy-rScl proteins and rScl-r␣ 2 I complexes were rotary shadowed and analyzed by EM as described previously (17,20). Briefly, recombinant proteins were dialyzed against 0.1 M sodium bicarbonate containing 1 mM magnesium chloride.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 The few collagen-like structures from pathogenic species that have been well studied suggest that the collagen motif is typically associated with the outer membrane of the bacteria, and may interact with the host to assist invasion or to help a pathogen evade the host immune system. 28 This binding can be, for example, to integrin receptors 29 or to other extracellular matrix molecules, mediating pathogen internalization by human cells. 30 The identification of this new group of collagens provides potential for development of new, recombinant biomedical materials.…”
Section: Recombinant Bacterial Collagen: An Emerging Systemmentioning
confidence: 99%